USING OF INFORMATIONAL TECHNOLOGIES FOR REGISTRATION OF RESEARCH AND DEVELOPMENT WORKS - V. A. Rusetsky (Литьë и металлургия)
The matters of creation and introduction of informational control systems at enterprises are considered. The necessity of using of such systems both for managers and analysts is analyzed. The limitations which are put at working with close research themes are considered additionally.